Analyzing The Success Of Whistle-Blowing System Users In Bolaang Mongondow Province Using The Information System Success Model - Glenn David Paulus Maramis (Universitas Sebelas Maret, 2025)
The effectiveness of a Whistleblowing System (WBS) is crucial for ensuring transparency and accountability in government institutions. This study evaluates the success of the WBS in Bolmong Governance using an extended Information System Success Model (ISSM), incorporating elements from the Technology Acceptance Model (TAM) and Trust as key determinants of User Satisfaction. The study examines the relationships between System Quality (SQ), Information Quality (IQ), and Service Quality (ServQ) as independent variables, while Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) function as mediating variables, ultimately influencing Trust (T) and User Satisfaction (US).A quantitative research approach was employed, with 100 participants selected through purposive sampling. Data was collected using a structured Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) in SmartPLS 3.0. The findings confirm that Information Quality, Perceived Ease of Use, Perceived Usefulness, and Trust significantly influence User Satisfaction, while Service Quality does not exhibit a significant impact. These results validate the Technology Acceptance Model (TAM) by demonstrating that PEOU and PU play crucial roles in system adoption and satisfaction.The study highlights the importance of ensuring data accuracy, usability, and trust in the successful implementation of WBS. Policymakers and system developers should focus on enhancing information quality and building trust to improve adoption and effectiveness. Future research should explore additional external factors, such as organizational support and regulatory compliance, to further refine the WBS success model.